EFFECT FOLIAR SPRAYING OF ASCORBIC ACID ON FLOWERING GROWTH AND YIELD CHARACTERISTICS OF TWO VARIETIES OF (Cucurbita pepo. L) UNDER PLASTIC HOUSE - Hussein , Ahlam Ahmed (Journal of agricultural, environmental and veterinary sciences, 2018)
The experiment was carried out in one of the plastic houses of the research station belong to the Department of Horticulture and Landscaping/ College of Agriculture/ Diyala University during the season 2017- 2018 to study effect foliar spraying of Ascorbic acid three concentrations (0, 50, 100 mg L- 1) on flowering growth and yield traits of two Hybrids of summer squash (F1 Carisma V1 and F1 Alexandria V2) under plastic houses conditions. The experiment included 6 treatments. Randomized Complete Block Design (RCBD) was used with three replicates; therefore, the number of pilot unit was 18 and each one included 10 plants. The results showed that the Hybrid V2 was superior in all of flowering growth such as (number of male and female flowers, sexual ratio and set ratio) as recorded (26.10 flower. plant- 1, 24.94 flower. plant- 1, 1.04 and 67.00) respectively and most of yield characteristic such as (fruit number, yield per plant and Total yield) as recorded (8.63 fruit. plant- 1, 1.733 kg. plant- 1 , 2.911 ton. house- 1) respectively. The Ascorbic acid treatment S3 (100 mg L- 1) and interpenetration between F1 Alexandria V2 and (100 mg L- 1) Ascorbic acid are superiority and gave the best results in all flowering growth and yield characteristic was significant of other treatments. But all of these treatments outperformed on control treatment which gave lowest rates for these traits.